(untitled) (World Bulletin of Management and Law, 2022)
This article analyzes some of the foundations of the institution of terminating the criminal case without solving culpability issues by implementing the advanced foreign experience in the criminal procedural legislation at the stage of judicial reforms and studies the problems related to the application of these cases. In the article, based on the views and ideas put forward by scientists, the ground of terminating the criminal case without solving culpability issues was analyzed through scientific, theoretical, practical, and legal norms. Based on the results of the analysis, appropriate suggestions and recommendations were developed to improve the institution of terminating the criminal case without solving culpability issues